METODE ANALYTICAL HIERARCHY PROCESS DALAM SISTEM PENDUKUNG KEPUTUSAN PENYARINGAN BAKAL CALON KEPALA DESA - Sukadi; Fardiana Karuniawati; Seno Aji (Jurnal Qua Teknika, 2024)
The aim of this research is to design a system using the Analytical Hierarchy Process method in a decision support system for screening prospective village heads. The research method used is SDLC with the waterfall model, because in this research designing a system, the waterfall method only reaches the system design stage. The research resulted in a system design using the Analytical Hierarchy Process method in a decision support system for screening prospective village head candidates which is expected to provide an overview to the regional government or village government in carrying out additional selection for prospective village head candidates